The unlikely tale of Chase & Finnegan - Warga, Jasmine (Balzer + Bray, 2026)
Told in two voices, Finnegan, a rescue dog mourning the loss of his previous life, is paired with Chase, a young orphaned cheetah, and together the two learn to trust again while discovering friendship and family.